BRS 369RF and BRS 370RF: Glyphosate tolerant, high-yielding upland cotton cultivars for central Brazilian savanna - Morello,Camilo de Lelis (2015)
Abstract BRS 369RF and BRS 370RF were developed by the EMBRAPA as a part of efforts to create high-yielding germplasm with combinations of transgenic traits. BRS 369RF and BRS 370RF are midseason cultivars and have yield stability, adaptation to the central Brazilian savanna, good fiber quality and tolerance to glyphosate herbicide.